A study of performance appraisal and its' effect on job satisfaction of employees in Shell Malaysia Borneo Region/ Fatihah Nur'addin Hamdan - Hamdan, Fatihah Nur'addin (2015)
Performance appraisal and job satisfaction have a positive relation towards each other. Every now and then, these 2 topics are a must to talk about in any organizations, not only the public sector but also private sector. Performance appraisal often linked to rewards, incentive, bonuses, and increment while job satisfaction is linked to the emotions, needs, thought and rationality. Job satisfaction is the main contributor in an organization business mission as it is related to the company's performance, revenues and target setting. Positive feedback of performance appraisal determines the level of job satisfaction of the employees. We often heard about employees who are not satisfied with the performance appraisal system due to a few reason and one of them is no face to face discussion on yearly performance with the supervisor, resulting the employee to have dissatisfaction feeling over the rewards or bonus that he or she received. So, the main reason to conduct this study is to determine the relationship between performance appraisal and job satisfaction as we want to see how far Performance appraisal has an effect on job satisfaction. This scope of this study is the employees of Shell Malaysia - Borneo. Minnesota Satisfaction Questionnaire - Short Version by Weiss et al. is use to test the employees job satisfaction towards the performance appraisal. Data is gathered from 142 respondents from Shell Malaysia Borneo Region. The findings were share with the Human Resource Department in Shell Malaysia Trading for internal use. Quantitative analysis has been carried out on this data. The SPSS 20 was used to measure the statistical for the quantitative portion and developed a structured table to categorized qualitative information. From the findings, it is proven that performance appraisal system has the influence over job satisfaction of the employees. Therefore, the findings from this study is hope can contribute to the the positive climate inside the organization in near future.